Implementation of Environmental Sanitation and Disinfection in Hospitals to Reduce the Spread of Covid19: A Literature Review - Devi Anggraini; Kusuma Secorpia Lestari (Universitas Airlangga, 2022)
Introduction: SARS-CoV-2 is a new variant of virus that attacks the human respiratory tract which was declared by WHO as a Covid19 pandemic. Covid19 transmission through solid surfaces, air, and waste occurring in hospital areas require disinfection and sanitation monitoring to ensure that new clusters are not created and outpatients are not infected with the SARS-CoV-2 virus in hospitals. Discussion: Using literature review method, 11 relevant articles that meet the inclusion criteria were selected. In the results of the study, there was a collection of samples in the solid surfaces, air and waste in both medical and non-medical areas containing SARS-CoV-2 RNA. The common objects where SARS-CoV-2 was discovered include doorknobs, toilet bowls, toilet flush buttons, and medical devices. In non-medical areas, the objects include computer keyboards, mice, and monitors. Chlorine-based disinfection for surfaces, monitoring in environmental sanitation by changing pillow and bedsheets and cleaning tables regularly were subsequently implemented. Conclusion: The implementation of environmental sanitation and disinfection is effective in eliminating the SARS-CoV-2 virus in hospitals. Studies indicated that disinfection is 95% to 99.99% effective in eliminating the SARS-CoV-2 virus. In addition, the SARS-CoV-2 virus was not discovered in isolation rooms but was located in other public hospital areas.